Towards deep learning based smart farming for intelligent weeds management in crops - Saqib, Muhammad Ali; Aqib, Muhammad; Tahir, Muhammad Naveed; Hafeez, Yaser (Frontiers in Plant Science, 2023)
Deep learning (DL) is a core constituent for building an object detection system and provides a variety of algorithms to be used in variety of applications. In agriculture, weed management is one of the major concerns, weed detection systems could be of great help to improve production. In this work, we have proposed a DL-based weed detection model that can efficiently be used for effective weed management in crops. Our proposed model uses Convolutional Neural Network based object detection system You Only Look Once (YOLO) for training and prediction. The collected dataset contains RGB images of four different weed species named Grass, Creeping Thistle, Bindweed, and California poppy. This dataset is manipulated by applying LAB (Lightness A and B) and HSV (Hue, Saturation, Value) image transformation techniques and then trained on four YOLO models (v3, v3-tiny, v4, v4-tiny). The effects of image transformation are analyzed, and it is deduced that the model performance is not much affected by this transformation. Inferencing results obtained by making a comparison of correctly predicted weeds are quite promising, among all models implemented in this work, the YOLOv4 model has achieved the highest accuracy. It has correctly predicted 98.88% weeds with an average loss of 1.8 and 73.1% mean average precision value. In the future, we plan to integrate this model in a variable rate sprayer for precise weed management in real-time.